Computer networks and inventive communication technologies proceedings of third ICCNCT 2020 - Smys, S.; Palanisamy, Ram; Rocha, Álvaro; Beligiannis, Grigorios N. (Lecture Notes on Data Engineering and Communications Technologies, 2021)
This book is a collection of peer-reviewed best selected research papers presented at 3rd International Conference on Computer Networks and Inventive Communication Technologies (ICCNCT 2020). The book covers new results in theory, methodology, and applications of computer networks and data communications. It includes original papers on computer networks, network protocols and wireless networks, data communication technologies, and network security. The proceedings of this conference is a valuable resource, dealing with both the important core and the specialized issues in the areas of next generation wireless network design, control, and management, as well as in the areas of protection, assurance, and trust in information security practice. It is a reference for researchers, instructors, students, scientists, engineers, managers, and industry practitioners for advance work in the area.